CompTIA A+ review guide exam 220-901, exam 220-902 - McMillan, Troy (Sybex, a Wiley brand, 2016)
The CompTIA A+ Complete Review Guide, 3rd Edition is your ideal solution for preparing for exams 220-901 and 220-902. The perfect companion to the CompTIA A+ Complete Study Guide, 3rd Edition this book provides you with extra review and reinforcement of key topics you'll see on the exam. The material is broken into two parts that each focus on a single exam, then organized by domain objective so you can quickly find the information you need most. This new third edition has been updated to reflect the revised exams, with the latest best practices and an emphasis on Windows 8/8.1 and mobile OSes. You also get access to the exclusive Sybex online learning environment featuring over 170 review questions, four bonus exams, 150 electronic flashcards, and a glossary of key terms - over 500 practice questions in all!